Visual Promotional Materials in Festival Branding: A Case Study of Nottingham Riverside Festival - liu, dingling (2016)
Tourism has rapidly grown into the world’s largest service sector industry as the business of attracting visitors and catering to their needs. Events such as festivals are a significant motivator of local tourism. Meanwhile, with the growing number of festivals and intense competition in the tourism industry, branding has become increasingly essential for a festival. The Riverside Festival is one of Nottingham’s biggest annual festivals held along the banks of the River Trent, at Victoria Embankment, adjacent to Trent Bridge, offering three days of family entertainment, which largely contributes to Nottingham tourism. This year, Nottingham City Council plans to change the artwork that has been used for many years to portray the event in the best light and the new 2016 artwork will contribute to the branding of Riverside Festival. Most of the existing literature focuses on using the festival as a tool for destination branding rather than branding itself, and the role and influence of visual promotional materials in festival branding is poorly understood. Therefore, further research into the proper means to use visual promotional materials to brand a festival is needed. This dissertation aims to evaluate Nottingham City Council’s 2016 festival artwork for Riverside Festival, and explore the influence of visual 1 promotional materials on festival branding. Content analysis and semiotic analysis have been applied to compare the 2016 artwork and 2015 artwork. An in-depth interview with an officer of communications and marketing department in Nottingham City Council provides more details of the process of developing the new artwork and ideas behind it. Also, a convenience sample of 200 attendees drawn from the 2016 Nottingham Riverside Festival is used for exploring visitor’s preferences towards 2015 and 2016 festival posters and their perceptions in the study. This dissertation gives new perspectives for festival branding, particularly for local and regional festival. Recommendations for artwork designing and promoting have been made for Nottingham City Council based on the findings.